"Truth is Held in Disrepute": O. Henry and the Dismantling of Paradigms - Aguilera Linde, Mauricio D. (Miscelánea: A Journal of English and American Studies, 2008)
Destabilization of principles and suspension of widely accepted beliefs pervade the conflicting ideological panorama of the Progressive Era. In a world dominated by the uprooting of long established traditions, O. Henry’s short fiction becomes the site wherein Darwin-dictated principles, gender roles and genre rules are either dislocated or subverted. Following Boris M. Ejxenbaum’s idea (1927) that the writer’s use of parody lays bare the construction of his stories, I propose to demonstrate that an intentional breaking of generic expectations lies behind the narrator’s use of multifarious literary formulas. Evolutionist axioms are also overruled, for dysgenic and not eugenic prevails over in the American society presented by the Southerner writer. Finally, by applying Veblen’s sociological ideas (1899) to O. Henry’s characters, I also aim to show that any attempt to classify them into types whose response can be predicted in the social contest is destined to fail.